Gender Fluidity: Sebuah Tinjauan Antropologi Kristiani - Derian, Mikhael Varian Toar (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
The discussion around gender is one of the most lively, complex and sensitive topics of the 21th century. Recently, for example, a term called: ‘gender fluidity’ has emerged. Gender fluidity is a new variation of the idea of gender that rejects a definitive gender categorization. What is the fundamental idea of ‘gender fluidity’? Is it true that gender is not definive? What is the true definition of gender? What is its difference to sex? With this paper, the author wants to study the phenomenon of ‘gender fluidity’ in the light of Christian anthropology based on the story of the creation and the redemption of man.